2020
DOI: 10.1136/archdischild-2019-318559
|View full text |Cite
|
Sign up to set email alerts
|

Use of oximetry to screen for paediatric obstructive sleep apnoea: is one night enough and is 6 hours too much?

Abstract: IntroductionNocturnal pulse oximetry can be used to screen for obstructive sleep apnoea (OSA) using the McGill Oximetry Score (MOS). The MOS has a time threshold for a technically adequate study of 6 hours. It has been suggested that one night of oximetry is sufficient to screen for OSA using the MOS.Aims(1) To evaluate night-to-night variation of the MOS. (2) To determine the impact of recording three nights of oximetry on the screening yield for OSA. (3) To explore whether useful MOS data are discarded when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Increasing the number of nights studied from one to three in a cohort of 329 paediatric patients undergoing nocturnal oximetry, including children with Down syndrome (n=34), typically developing children (n=204) and children with other predisposing factors to OSA (n=82), increased the diagnostic yield from 38% (n=126) on night one to 59% (n=195) by night three. There was a reduction in the number of patients without adequate data for analysis from 16% on night one to 6% following night three [ 86 ].…”
Section: Night-to-night Variability In Paediatric Sleep Parametersmentioning
confidence: 99%
“…Increasing the number of nights studied from one to three in a cohort of 329 paediatric patients undergoing nocturnal oximetry, including children with Down syndrome (n=34), typically developing children (n=204) and children with other predisposing factors to OSA (n=82), increased the diagnostic yield from 38% (n=126) on night one to 59% (n=195) by night three. There was a reduction in the number of patients without adequate data for analysis from 16% on night one to 6% following night three [ 86 ].…”
Section: Night-to-night Variability In Paediatric Sleep Parametersmentioning
confidence: 99%
“…Recent British Thoracic Society consensus recommends a single night of pulse oximetry monitoring to diagnose severe OSA in TD children 2. Children with complex medical conditions demonstrate night-to-night variability in saturation indices, and multiple nights of monitoring requires consideration 8 9. Future research is necessary to determine the most consistent saturation indices for diagnostic reporting.…”
Section: Pulse Oximetrymentioning
confidence: 99%
“…PAVONE et al [35] have provided evidence that between-night pulse oximetry metric variations are limited in children without comorbidities. However, GALWAY et al [36] showed that there is likely to be night-to-night variability for children with comorbidities. Further research is required to determine which oxygen saturation indices demonstrate least night-to-night variability and thus might prove most useful diagnostically.…”
Section: Pulse Oximetrymentioning
confidence: 99%